BIFURCATION OF SUPERIOR ARTICULAR FACETS OF ATLAS VERTEBRA: A CASE STUDY IN DRY BONES - MOHANTY, SMRUTI REKHA; PANIGRAHI, MAMTA; SENAPATI, SUSMITA; SN, SAMAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to see the superior articular facets (SAF) of atlas vertebrae for complete bifurcation. Methods: In a number of 50 atlas vertebrae with 100 SAF were studied for the tendency to complete separation in the Department of Anatomy and Forensic Medicine of Kalinga Institute of Medical Sciences, Bhubaneswar during the period of January 2015 to January 2016. Results: Out of 50 atlas vertebrae (100 AF), we observed complete bifurcation on both sides in 14 atlas vertebrae (28 sides) and complete bifurcation right side only in six atlas vertebrae and complete bifurcation left side only in 14 atlas vertebrae. The results were compared with those of other studies and were statistically analyzed. Discussion: The clinical significance of this study has been thus discussed with a reference to its possible effect on the restriction of the neck movement at the atlanto-occipital joint. Conclusion: This study is of great importance to the clinicians for doing any clinical facet procedure in the neck region.